Exploring tax policy to advance population health, health equity, and economic prosperity : proceedings of a workshop - Wizemann, Theresa M. (The National Academies Press, 2019)
The National Academies of Sciences, Engineering, and Medicine's Roundtable on Population Health Improvement has been focused on the subject of dependable resources for population health since its inception in 2013. On December 7, 2017, the roundtable convened a workshop to explore tax policy as it relates to advancing population health, health equity, and economic prosperity. This publication summarizes the presentations and discussions from the workshop.